2011
DOI: 10.1038/ajh.2011.30
|View full text |Cite
|
Sign up to set email alerts
|

Association of Sarcoidosis With Endothelial Function, Arterial Wall Properties, and Biomarkers of Inflammation

Abstract: In the present study, we have shown that sarcoidosis patients have impaired endothelial function and increased arterial stiffness. Sarcoidosis patients on cortisone treatment had no differences compared to controls on the vascular parameters. Moreover, there was a significant correlation between inflammatory process and vascular function impairment. These findings indicate that sarcoidosis patients have impaired vascular function and increased inflammatory status, which may improve with cortisone treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 48 publications
2
22
0
2
Order By: Relevance
“…In line with our results, Siaos et al 6 also revealed increased arterial stiffness in patients with sarcoidosis compared with healthy controls, evaluating the AI75. However, in contrast to our study, PWV values were not significantly different in the study groups.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…In line with our results, Siaos et al 6 also revealed increased arterial stiffness in patients with sarcoidosis compared with healthy controls, evaluating the AI75. However, in contrast to our study, PWV values were not significantly different in the study groups.…”
Section: Discussionsupporting
confidence: 81%
“…However, Siasos et al 6 showed that patients on cortisone treatment have the same vascular parameters as healthy controls. Therefore, the increased PWV in our patients may result from systemic intimal and medial infiltration of the vasculature by a noncaseating granuloma.…”
Section: 5mentioning
confidence: 99%
See 2 more Smart Citations
“…Endothelial function was evaluated by estimating the flow mediated dilation (FMD) in the brachial artery, as previously described [13][14][15]. Endotheliumindependent dilation was defined as the %change of vessel diameter from rest to the maximum diameter post-nitrate administration.…”
Section: Evaluation Of Endothelial Functionmentioning
confidence: 99%